Entre a retórica do impeachment e a do golpe: análise do conflito de lógicas argumentativas na doxa política brasileira - Rodrigo Seixas Pereira Barbosa (2019)
Former President Dilma Rousseff's impeachment widened and deepened old dissensions in Brazil, resurgent because they were never cured, which were evidenced by the alleged polemic motivation to open the process. For the supporters, by the way, the process was a legitimate impeachment, with solid foundations based on legality. For the opposites, the process was a coup d’État (just coup, in this case), because, besides being lacking in legality, was designed by politicians dissatisfied with the direction of the government, thus conspiring for the deposition of the president. Given this scenario, although different doxas were mobilized to justify the process, it was possible to realize that the arguments of the opinants, favorable and contrary to the deposition, were especially standardized, with the same types of arguments and the same nature of relationship between the argument and the conclusion, thus revealing an insurmountable dialogues of the deaf that seem to trace back a profound history of conflict between two distinct ways of understanding political and social reality. Identifying, therefore, a certain doxic logic in all the analyzed arguments, the present research was based on Marc Angenot's thesis of argumentative logics with the aim of investigating, through the doxic schematization of arguments, the logical-argumentative nature of the opinions surrounding of impeachment. Thus, starting from argued opinions published through different textual- discursive genres (all of them opinatives: editorials, opinion articles, open letter and manifest) this research sought, through rhetorical-argumentative analysis, to investigate the construction of justification of the positions on either side of the polemic, a justification that always concludes as a qualification to the detriment of another: it was a coup or an impeachment. In this sense, in theoretical-methodological terms, one combines the assumptions of Angenot's antilogical rhetoric, as well as his rhetoric of qualification, with the assumptions of (discursive) -argumentative analysis, especially as proposed by Christian Plantin and Ruth Amossy. After the results achieved by the analysis, it was argued that the conceptual words coup and impeachment are presented as argumentative condensates of all argumentative logic and also the values present in each doxa pro and against the destitution. Thus, in demanding to unveil what is partially hidden, an interpretation was finally proposed by means of a rhetoric- discursive hermeneutic device that made it possible to understand, more comprehensively, the semantic-argumentative implications that the enunciation of the words coup and impeachment bring to speech. Therefore, as it is a work about such a recent event in our political history, this thesis intended to contribute to a better understanding of Dilma Rousseff's impeachment and its implications for Brazilian society.